MANAJEMEN BIMBINGAN DAN KONSELING DI SMA MA’ARIF NGAWI - KHOLIFATUL KHASANAH (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2019)
Implementation of guidance and counselling in educational planning required management guidance and counselling that is well-systemized by the parties providing guidance and counselling in schools. Therefore it becomes interesting for researchers to research educational institutions in Ma'arif Ngawi High School. From the background picture behind the formulation of the problem that arises is how is the process of planning, organizing, implementing, to supervising or evaluating guidance and counselling that is applied at Ma'arif Ngawi High School. This research is qualitative. The informants of this study were the guidance and counselling teacher at Ma'arif Ngawi High School. The research data collection method was conducted by interview, observation, and documentation. Data analysis was performed with qualitative analysis which included data collection, data education, data presentation and conclusion collection. The results of this published research on Ma'arif High School apply guidance and counselling management in providing services to students. Proven in terms of planning, Maakah High School explained several processes that discuss the needs of students, the school needs analysis, setting goals, choosing the type of service, determining the time and place of activity, and determining facilities and budgets. The organizing phase also involves several processes of the division of guidance and counselling tasks, socialization of work methods, and coordination with stakeholders. The implementation phase of the process is following the planning that has been prepared following the program that has been designed. However, the implementation of the program based on research, namely the implementation of the wrong service program. Finally, the review also discusses the process of evaluating work results, evaluating work results and making decisions for improvement and development.